Political risk, security and geopolitics: Latin America and the US –China strategic competition - Carbajal-Glass, Fausto (FLACSO - Sede Ecuador, 2023)
The objective of this article is to explore the implications that the global strategic competition between the United States and China can have –and is already having– in Latin America and the Caribbean, a region that is in the middle of this great power competition, for economic, trade, political-diplomatic or technological reasons. From an integrative, transdisciplinary and strategic approach, the ramifications of the rivalry between the United States and China in the Western Hemisphere are analyzed. The methodology is based on case studies that make visible the implications of this phenomenon while contributing to the construction of generalizable knowledge and the identification of patterns in Latin America and the Caribbean. It is concluded that the global strategic competition between Washington and Beijing is feeding, voluntarily or involuntarily, pre-existing dynamics of political instability, social conflict and armed violence in Latin American countries.